Intersections of climate, security and human mobility in the community of Cedeño, Marcovia, department of Choluteca, Honduras - Palou-Zuniga, Nohelia; Higuera-Florez, Julian (2025)
Recent research has determined the importance of analyzing the relationship between climate variability and the dynamics of insecurity, violence and human mobility in Honduras and other countries in the region. Most of these efforts tend to focus on data and studies that demonstrate the correlations between these variables at the regional or national level in order to inform programs and strategies for climate change, citizen security, migration, displacement, natural resource management, food security, among others. However, this study aims to make a local level analysis of these interrelationships to capture the climatic, environmental, social, economic and cultural specificities of a single community: Cedeño, municipality of Marcovia, department of Choluteca. This proposal aims to highlight the importance of understanding local specificities in order to inform as accurately as possible the eventual policies, programs, strategies or interventions designed for the region.